Biologics targeting IL-17 sharply reduce circulating T follicular helper and T peripheral helper cell sub-populations in psoriasis - Tsiogkas, Sotirios G.; Mavropoulos, Athanasios; Dardiotis, Efthimios; Zafiriou, Efterpi; Bogdanos, Dimitrios P. (Frontiers in Immunology, 2024)
Introduction: Circulating T follicular helper cells (cTfh) and circulating T peripheral helper (cTph) cells (which share common characteristics with the cTfh population) are implicated in the pathogenesis of immune-mediated and autoimmune diseases such as psoriasis (Ps). Their close interplay with the IL-17 axis and their ex vivo influence by anti-Il-17 targeting biologic agents used to treat Ps are elusive. This study aimed to investigate the effect of biologics targeting IL-17 on cTfh and cTph cell subpopulations isolated from the blood of patients with Ps at baseline and three months post-treatment initiation.Methods: Peripheral blood mononuclear cells (PBMCs) were isolated from patients with Ps at treatment initiation and three months later. Samples were also collected from controls. Cells were stained using monoclonal antibodies. Flow cytometry assessed cells' fraction of cTfh (CD3 + CD4 + CXCR5 + ) and cTph (CD3 + CD4 + CXCR5 -PD-1 hi ).Results: Flow cytometric analysis showed increased fractions of activated cTfh subsets including ICOS + and ICOS + PD-1 + expressing cells, in patients compared to controls. Biologic blocking of IL-17A diminished the cTfh population. Furthermore, ICOS + and ICOS + PD-1 + sub-populations were also inhibited. Finally, the cTph cell fraction significantly decreased after three months of successful treatment with biologics. Conclusion: Early anti-IL-17-mediated clinical remission in Ps is associated with 31 decreased cTfh and cTph cell subpopulations. 32